Juhūd al-Mu’allimah fī Tarqiyah Mahārah al-Kalām lada Ṭullāb Ma’had Roudhotul Jannah bi Pagaran Batu Padang Lawas al-Syamāliyyah - Endang Safitri Hutapea; Ira Aniati; Erawadi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Many students still experience difficulties in communicating in Arabic, as reflected in their low participation in classroom discussions and their hesitation to interact with teacher. The improvement of speaking skills is closely related to the efforts made by teacher in the learning process. This study aims to analyze teacher’s efforts in improving students’ speaking skills and to identify the obstacles faced by teacher in enhancing students’ speaking skills at Roudhotul Jannah Boarding School. This study employed a qualitative research design with a descriptive approach. Data were collected through classroom observations during Arabic language learning activities and interviews with Arabic language teacher and students. The findings reveal that teacher’s efforts to improve students’ speaking skills are carried out through three main aspects: the implementation of Arabic language environment, the use of various teaching methods, and the application of appropriate learning strategies. Teacher also motivate students by consistently using Arabic in daily communication, providing appreciation for students who actively speak Arabic, and encouraging students’ confidence to communicate in Arabic. However, teacher face several obstacles in improving students’ speaking skills, including limited learning media, students’ difficulties in reading Arabic texts, differences in students’ levels of understanding, and students’ shyness in speaking Arabic.